Elevated plasma heparin-binding protein is associated with early death after resuscitation from cardiac arrest. Issue 1 (December 2016) - Ristagno, Giuseppe; Masson, Serge; Tiainen, Marjaana; Bendel, Stepani; Bernasconi, Roberto; Varpula, Tero; Milani, Valentina; Vaahersalo, Jukka; Magnoli, Michela; Spanuth, Eberhard; Barlera, Simona; Latini, Roberto; et al.
Abstract Background An intense systemic inflammatory response is observed following reperfusion after cardiac arrest. Heparin-binding protein (HBP) is a granule protein released by neutrophils that intervenes in endothelial permeability regulation. In the present study, we investigated plasma levels of HBP in a large population of patients resuscitated from out-of-hospital cardiac arrest. We hypothesized that high circulating levels of HBP are associated with severity of post-cardiac arrest syndrome and poor outcome. Methods Plasma was obtained from 278 patients enrolled in a prospective multicenter observational study in 21 intensive care units (ICU) in Finland. HBP was assayed at ICU admission and 48 h later. Multiple organ dysfunction syndrome (MODS) was defined as the 24 h Sequential Organ Failure Assessment (SOFA) score ≥ 12. ICU death and 12-month Cerebral Performance Category (CPC) were evaluated. Multiple linear and logistic regression tests and receiver operating characteristic curves with area under the curve (AUC) were performed. Results Eighty-two percent of patients (229 of 278) survived to ICU discharge and 48 % (133 of 276) to 1 year with a favorable neurological outcome (CPC 1 or 2). At ICU admission, median plasma levels of HBP were markedly elevated, 15.4 [9.6–31.3] ng/mL, and persisted high 48 h later, 14.8 [9.8–31.1] ng/mL. Admission levels of HBP were higher in patients who had higher 24 h SOFA and cardiovascular SOFA score (p  < 0.0001) and in those who developed MODS compared to those who did not (29.3 [13.7–60.1] ng/mL vs. 13.6 [9.1–26.2] ng/mL, p  < 0.0001; AUC = 0.70 ± 0.04, p  = 0.0001). Admission levels of HBP were also higher in patients who died in ICU (31.0 [17.7–78.2] ng/mL) compared to those who survived (13.5 [9.1–25.5] ng/mL, p  < 0.0001) and in those with an unfavorable 12-month neurological outcome compared to those with a favorable one (18.9 [11.3–44.3] ng/mL vs. 12.8 [8.6–30.4] ng/mL, p  < 0.0001). Admission levels of HBP predicted early ICU death with an AUC of 0.74 ± 0.04 (p  < 0.0001) and were independently associated with ICU death (OR [95 %CI] 1.607 [1.076–2.399], p  = 0.020), but not with unfavorable 12-month neurological outcome (OR [95 %CI] 1.154 [0.834–1.596], p  = 0.387). Conclusions Elevated plasma levels of HBP at ICU admission were independently associated with early death in ICU.